PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Kumara Dewi, Winona; Wahyuni EDT, Risa; Sephia Muchda, Anisa (Universitas Sumatera Barat, 2024)
Tax aggressiveness is a strategy employed by companies to minimize the tax burden they will incur by engaging in tax planning, using either legal methods (tax avoidance) or illegal methods (tax evasion). This study aims to examine the effect of Profitability and Leverage on Tax Aggressiveness, tested both partially and simultaneously. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. The data in this study is secondary data sourced from the company's annual financial statements, and the type of research is quantitative. The population in this study consists of 59 manufacturing companies with a total sample of 177 financial statements over a 3-year research period. The hypothesis in this study was tested using multiple linear regression techniques with SPSS version 16. The sampling technique in this study used purposive sampling. The results of this study indicate that the Profitability variable partially has a positive effect on Tax Aggressiveness, Leverage partially does not affect Tax Aggressiveness, while simultaneously, the Profitability and Leverage variables together have an effect on Tax Aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange for the period 2021 – 2023.